2021
DOI: 10.2196/29195
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Opinions on Working From Home in the United States During the COVID-19 Pandemic: Observational Study

Abstract: Background Since March 2020, companies nationwide have started work from home (WFH) owing to the rapid increase of confirmed COVID-19 cases in an attempt to help prevent the disease from spreading and to rescue the economy from the pandemic. Many organizations have conducted surveys to understand people’s opinions toward WFH. However, the findings are limited owing to a small sample size and the dynamic topics over time. Objective This study aims to und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…While not within the scope of our project, in reviewing the literature, we found a few additional areas of interest. One area that we did not capture in our research: Why do older workers with higher incomes prefer WFH initiatives ( Xiong et al 2021 )? Is this because they have already climbed the career ladder and are comfortable in their positions, or is there another less obvious reason that contributes to this situation?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not within the scope of our project, in reviewing the literature, we found a few additional areas of interest. One area that we did not capture in our research: Why do older workers with higher incomes prefer WFH initiatives ( Xiong et al 2021 )? Is this because they have already climbed the career ladder and are comfortable in their positions, or is there another less obvious reason that contributes to this situation?…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the women in their sample reported reduced work hours, which may explain why they reported more positive opinions about WFH as it allowed them to spend more time with family, especially children. Interestingly, they also found that older workers with higher incomes tend to hold more positive opinions on WFH ( Xiong et al 2021 ). While analyzing worker productivity of WFH during the pandemic, other researchers found similar findings.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Social platforms have abundant multimodal data. The publicly available profile image uploaded by a user may contain the demographic information of this user (Lyu et al, 2020 ; Xiong et al, 2021 ; Zhang X. et al, 2021 ). This side information can potentially improve the performance of measuring human behavior.…”
Section: Using Big Data To Measure Human Behavior In Covid-19mentioning
confidence: 99%
“…Social platforms have abundant multimodal data. The publicly available profile image uploaded by a user may contain the demographic information of this user (Xiong et al 2021;Zhang, Lyu, and Luo 2021;Lyu et al 2020). This side information can potentially improve the performance of measuring human behavior.…”
Section: Multimodal Datamentioning
confidence: 99%